Pendampingan Penggunaan Aplikasi Digital Qris Sebagai Alat Pembayaran dan Pengembangan Promosi Secara Digital pada UMKM Reni Allshop - Tina Lindriani; Selvi Marlianti; Tiara Lestari; Nonie Afriyanty; Herlina Yustati (PT Pustaka Cendekia Publisher, 2025)
MSMEs play an important role in supporting national economic growth, but many business actors still do not understand the importance of utilizing digital technology, both in payment systems and marketing strategies. This community service program aims to assist MSME Reni Allshop in implementing non-cash payment methods based on QRIS and developing promotions through digital marketing. The method used is Participatory Action Research (PAR), which actively involves MSME actors in the process of observation, problem formulation, solution solving, and implementation of actions. The results of this activity show a significant increase in the knowledge and skills of MSME actors in the use of QRIS as an efficient and secure payment system, as well as in managing social media as a means of promotion. MSME actors have succeeded in understanding the importance of content consistency, copywriting techniques, and optimizing digital platforms such as Instagram and WhatsApp. This program has been proven to have a positive impact on transaction effectiveness and marketing appeal, as well as increasing the professionalism and competitiveness of MSMEs in the digital era.